Cognitive skills improved by BrainWare SAFARI training program: Electroencephalographic study - Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: Executive functions have been shown to be related to academic achievement and the ability to learn. Understanding the role of executive function may offer new learning opportunities for children. The 2018-2019 implementation of BrainWare SAFARI pilot study started with primary school students achieving an average improvement in cognitive skill development. Aims and Objective: This study was set to find spatial ability and cognitive skill abilities done by letting students who performed spatial ability tasks after BrainWare SAFARI training exercises and also investigated by using the effectiveness of commercially available lightweight EEG device. Materials and Methods: Participants were selected to participate in the 2018-2019 pilot based on their average learning abilities. Results: All participants were able to complete the targeted number of sessions of BrainWare SAFARI. All participants showed significantly mean improvement of cognitive skills such as speed, memory, spatial ability, and problem solving, respectively. The cognitive performance increased statistically significant implying that all participants gained experienced significant improvements in multiple areas of cognitive processing. The attention and mediation levels as well as cognitive performance or cognitive skill improvement were changed with statistically significant at 0.05 level. The findings also showed that all brainwaves were increased with statistically significant while performing cognitive skills ability tasks. Conclusion: It is no doubt that all participants were able to complete all sessions of BrainWare SAFARI program. Practicing cognitive skills improvement games as BrainWare SAFARI could significantly increase alpha, theta and beta frequency bands. BrainWare SAFARI cognitive skills training could significantly improve cognitive performance in Thai children indexed by the electroencephalographic activities.